Learning Mastercam. - Hokanson, Taylor (linkedin.com, 2017)
Explore Mastercam, a computer-aided design and manufacturing (CAD/CAM) application. Learn how to convert a 3D model to a toolpath—a set of instructions for a CNC mill to follow.